Soybean extract increases telomerase reverse transcriptase protein expression in pancreatic β-cells of diabetes mellitus-induced rats (Medical Journal of Indonesia, 2019)
BACKGROUND A number of studies on the benefits of soybean (Glycine max (L.) Merr) in the treatment of diabetes mellitus (DM) have already been conducted; however, the effects of soybean extracts on telomerase reverse transcriptase (TERT) expression in improving telomerase activity in pancreatic cells is currently unknown. This study was aimed to evaluate the effects of soybean extracts on TERT protein expression in the pancreatic β-cells of rats with DM. METHODS Sixty male Sprague-Dawley rats were randomly divided into six groups: (1) negative control (N); (2) DM rats induced by alloxan (DMA); (3) DM rats with glibenclamide (DMG; positive control); (4) DM rats with 1 mg/kgBW/day soybean extract (DM1E); (5) DM rats with 5 mg/kgBW/day soybean extract (DM5E); (6) DM rats with 25 mg/kgBW/day soybean extract (DM25E). The treatments were carried out over 28 days. The measured variables included fasting blood glucose (FBG) level, TERT protein expression, and the number of pancreatic Î²-cells. RESULTS All parameters were measured against the diabetes control group. The FBG levels in rats DM1E, DM5E, and DM25E were significantly reduced on the 28th day (p < 0.05). TERT protein expression and the number of pancreatic β-cells (DM25E) also showed significant improvements compared to DM rats (p < 0.05). CONCLUSIONS Soybean extracts can increase TERT protein expression in pancreatic β-cells in diabetes-induced rats.